Negotiating Leadership in Interdisciplinary Co-Productive Research: A Case Study of An International Community-Based Project Between Collaborators From South Africa and the United Kingdom. (December 2020) - Hart, Angie; Biggs, Shahnaz; Scott-Bottoms, Stephen; Buttery, Lisa; Dennis, Scott; Duncan, Simon; Ebersöhn, Liesel; Flegg, Mirika; Kelso, Clare; Khaile, Neo Mosna; Mampane, Motlalepule Ruth; Mampane, Ngwanangwato Selogadi; et al.
In the absence of empirical and conceptual considerations of the negotiation of leadership in teams doing community-based research, this article adds to the leadership literature by offering a critical reflection on positioning and collaborative teams in the context of one interdisciplinary, co-productive, cross-generational and international research project. The project focused on youth and community resilience to drought in South Africa. Fourteen co-researchers reflected on their experiences of leadership within the project, using a collectively developed questionnaire. Findings uniquely highlight wider ethical considerations when youth and novice researchers are included in research teams. A strong emphasis on cultural responsiveness was found; with local and culturally led leadership seen to positively influence both processes and outcomes. Reflections suggest collaboration may be approached as an "ethos" and aided by transformational leadership theories and methodologies. Findings may be especially relevant to research teams, funders, and ethical bodies.